Principles of Sakha Language Terminology Description in Linguistics of 1920-1940 - Y. M. Borisova (Научный диалог)
The features of term studies formation in the works of researchers of the Sakha language in the 1920-1940-ies are considered. It is reported that at this time, a lot of work was done to develop the theoretical foundations and principles of creating the terms of the Sakha language, as well as a large number of terms in various fields of knowledge, especially in the socio-political sphere. It is emphasized that terminology complexes have been developed in all subjects in the volume of high school. It is shown that these goals were achieved relatively quickly because of the Yakut intelligentsia leaders of terms construction, who recognized the great importance of this work, enthusiastically took up the work and led others. Among leaders there were now well-known figures of language and - wider - cultural construction: A. E. Kulakovskiy, S. A. Novgorodov, A. A. Ivanov (Күндэ), G. V. Baishev (known by literary pseudonym Altan Saryn) and P. A. Oyunskiy. The article notes that each of these scientists went his own way, had his own priorities. Based on the results of the review, it is proved that the activity on the Yakut terminology system development was initially focused on two main ways of terminology fund formation: the use of internal language resources and borrowing of terms from other languages, in particular Russian. The article attempts to analyse dictionaries compiled by figures of linguistic construction of 1920-1940 from the point of view of the theory of modern thermography in order to optimize typical and composite parameters of terminological dictionaries.